PENGARUH PEMBERIAN PEMBENAH TANAH DAN PUPUK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) - saiful arif zain; Abdul Basit; Mahayu Woro Lestari (AGRONISMA, 2021)
This study aims to determine the effect of fertilizer and inorganic soil on the growth and yield of tomato plants (Lycopersicum esculentum Miil) in the field. The research was carried out in the experimental area of Merjosari sub-district, Malang City and the Integrated Laboratory of the Faculty of Agriculture, Islamic University of Malang. This study used a factorial randomized block design (RAK) consisting of 2 factors of soil concentration and dose of inorganic fertilizer with 12 treatments repeated 3 times. The results showed that the application of biological fertilizer 1ml/liter of water + 100% recommended dose of inorganic fertilizer (M2P1) was shown in the parameters of the number of leaves, fruit weight per plant and fruit weight per hectare, where plant productivity reached 24.98 tons/ha. However, it was not significantly different from the application of 0.5 ml/liter water + 50% inorganic fertilizer recommended dose (M1P3).